A sea urchin in vivo model to evaluate Epithelial‐Mesenchymal Transition. (24th April 2017) - Romancino, Daniele P.; Anello, Letizia; Lavanco, Antonella; Buffa, Valentina; Di Bernardo, Maria; Bongiovanni, Antonella
Abstract : Epithelial‐mesenchymal transition (EMT) is an evolutionarily conserved cellular program, which is a prerequisite for the metastatic cascade in carcinoma progression. Here, we evaluate the EMT process using the sea urchin Paracentrotus lividus embryo. In sea urchin embryos, the earliest EMT event is related to the acquisition of a mesenchymal phenotype by the spiculogenetic primary mesenchyme cells (PMCs) and their migration into the blastocoel. We investigated the effect of inhibiting the epidermal growth factor (EGF) signaling pathway on this process, and we observed that mesenchyme cell differentiation was blocked. In order to extend and validate our studies, we investigated the migratory capability and the level of potential epidermal growth factor receptor (EGFr) targets in a breast cancer cell line after EGF modulation. Altogether, our data highlight the sensitivity of the sea urchin embryo to anti‐EMT drugs and pinpoint the sea urchin embryo as a valuable in vivo model system for studying EMT and the screening of anti‐EMT candidates. Abstract : Epithelial‐mesenchymal transition (EMT) plays a central role both during development and in carcinoma progression and metastatic cascade; sea urchin embryos show an early physiologic EMT event related to the acquisition of a mesenchymal phenotype. We investigated the effect of inhibiting the EGF signaling pathway on EMT process in the sea urchin Paracentrotus lividus embryos and we extend and validate our studies in a breast cancer cell line. Our data pinpoint the sea urchin embryo as a valuable in vivo model system for studying EMT and the screening of anti‐EMT candidates.